Assessing the Predictive Value of Injury Severity Score (ISS) in Relation to Morbidity, Mortality, and Hospital Stay of Patients Following Road Traffic Accidents - Muhammad Nadeem, Shah Abbass, Haider Shah, Shahzad Khan, Anwar Ul Haq, Shahid Alam (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Road traffic accidents (RTAs) remain one of the leading causes of death and disability worldwide. The Injury Severity Score (ISS) is a well-established tool used to assess trauma severity and predict outcomes in trauma patients. It is widely applied in evaluating the severity of injuries in patients following RTAs. This study aims to assess the predictive value of the ISS in relation to morbidity, mortality, and hospital stay in RTA patients at a major trauma center. Methodology: This retrospective cohort study was conducted at a major trauma center over two years, from June 2023 to November 2023. A total of 92 patients involved in RTAs were included. Data were collected from the trauma registry, including demographic information, ISS scores, injury details (based on the Abbreviated Injury Scale - AIS), and clinical outcomes such as morbidity, mortality, and hospital length of stay. Statistical analysis was performed using SPSS, with Pearson’s correlation and multivariate regression used to assess relationships between ISS and outcomes. A p-value of <0.05 was considered statistically significant. Results: The study included 92 patients, with an average age of 42.1 years (range 19–89 years), and 68% of them were male. The mean ISS score was 17.8 ± 12.2. The mortality rate was 11%, with the highest mortality observed in patients with ISS scores greater than 25 (50% mortality). The morbidity rate was 27%, with a significant correlation between higher ISS scores and increased complications. The average hospital stay was 12.3 days, and longer stays were significantly associated with higher ISS scores (p < 0.05). Conclusion: The ISS is a reliable predictor of morbidity, mortality, and hospital stay in patients following road traffic accidents. Higher ISS scores are associated with increased mortality, complications, and prolonged hospital stays. The findings support the use of ISS as a useful tool for triaging and managing trauma patients, enabling clinicians to make better-informed decisions regarding patient care and resource allocation. Keywords: Injury Severity Score, Road Traffic Accidents, Morbidity, Mortality, Hospital Stay, Trauma, Predictive Value